Traces in the Landscape. Re-interpreting the Linear Infrastructure - Giovinazzi, Oriana; Giovinazzi, Gianvito (TeMA - Journal of Land Use, Mobility and Environment, 2011)
The gap between the infrastructure project and landscape design, between engineering works and quality of urban space, is a fact. The causes of poor integration are different, between these the indifference of the spaces of mobility with regard to nature and the stratification of places, the poverty figurative of many design solutions, the concept of a space transport as an element strictly monofunctional that usually does not integrate different uses and activities, as a purely technical solution to the shape of the city, almost never designed as an element of the regeneration of landscape, but as an exclusive place of movement and crossing. The infrastructure project is combined with the search for a new spatial quality, when the technical and morphological solutions conceive infrastructure not as an isolated element, foreign or superimposed on the context, but as part of the process of construction-regeneration of the landscape. In particular, the project for the rehabilitation and re-functionalization of linear infrastructures can become an opportunity to re-establish significant relations/interactions between parts of the city and territory, for the redevelopment and enhancement of places where the cultural and historical heritage and the landscape are a substantial source. The theme of inclusion of linear infrastructure in the landscape is declined in the following paragraphs by examining some experiences already implemented or being planned, extreme cases chosen according to their symbolism and the specific context, to assess the application and testing of innovative architectural designs and new planning proposals in areas which, although are confronted with problems related to lack of infrastructure and needs in the functional reorganization, appear to be highly stratified and places with substantial value and identity. The aim is to bring out the complexity of the search for design solutions for infrastructure that intersect very different situations and contexts (relations between “linear system”, “figures” and “sections”) where it is necessary to put together technical and constructive solutions with historical and/or morphological singularity, or infrastructure that represent and express themselves (also with the architectural choices) the context through enhancing the landscape, or infrastructure where is dominant the issue “perceptual”, the dynamic component or dimension of time, etc.